Remarks on quasilinear evolutions equations - James E. Munoz Rivera (International Journal of Mathematics and Mathematical Sciences)
In this paper we study the existence result of classical solutions for the quasilinear equation utt−Δu−M(∫Ω|∇u|2dx)Δutt=f, with initial data u(0)=u0, u(1)=u1 and homogeneous boundary conditions.